2015
DOI: 10.3390/proteomes3030283
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Mouse Tears and Saliva: Evidence from Large Protein Families for Functional Adaptation

Abstract: We produced a tear proteome of the genome mouse, C57BL/6, that contained 139 different protein identifications: 110 from a two-dimensional (2D) gel with subsequent trypsin digestion, 19 from a one-dimensional (1D) gel with subsequent trypsin digestion and ten from a 1D gel with subsequent Asp-N digestion. We compared this tear proteome with a C57BL/6 mouse saliva proteome produced previously. Sixteen of the 139 tear proteins are shared between the two proteomes, including six proteins that combat microbial gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 56 publications
1
20
1
Order By: Relevance
“…It is therefore likely, that LCN4 together with Vomeromodulin (Khew-Goodall et al, 1991) and MUP4 (Sharrow et al, 2002) participate in the process of pheromone access and detection by VNO. Following the process of pheromone detection, some of these proteins (LCN3, LCN4, VM, OBPs) are presumably transported to the oral cavity where they are often detected in saliva of C57BL/6 mice (Blanchard et al, 2015;Karn and Laukaitis, 2015) but, as we found in this study, their mRNAs are produced elsewhere (i.e., mainly VNO).…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…It is therefore likely, that LCN4 together with Vomeromodulin (Khew-Goodall et al, 1991) and MUP4 (Sharrow et al, 2002) participate in the process of pheromone access and detection by VNO. Following the process of pheromone detection, some of these proteins (LCN3, LCN4, VM, OBPs) are presumably transported to the oral cavity where they are often detected in saliva of C57BL/6 mice (Blanchard et al, 2015;Karn and Laukaitis, 2015) but, as we found in this study, their mRNAs are produced elsewhere (i.e., mainly VNO).…”
Section: Discussionmentioning
confidence: 51%
“…Similarly Obp5, Obp6, Obp7 are also highly expressed in lacrimal glands (Obp5 and Obp7 originally annotated in inbred C57BL/6 as Obp1a and Obp1b). Recently, OBP proteins have been identified in tears of the laboratory mouse C57BL/6 (Karn and Laukaitis, 2015). In this study, Obp transcripts seem to be co-expressed in combination with other lipocalins (e.g., nasal and lacrimal Obp5, Obp7, Mup4, and Lcn11).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The epinephrine and dopamine levels were below the detection limit, which is most likely due to the small volume of the collected samples (1 to 2 μL). There are methods to stimulate lacrimation in animals using cholinomimetics [14], but the composition of stimulated tear fluid is known to vary significantly [15].…”
Section: +2mentioning
confidence: 99%